Pengaruh Konsentrasi Maltodekstrin dan Glukomanan Terhadap Karakteristik Serbuk Minuman Instan Daun Jeruju (Acanthus ilicifolius L.) - Ida Ayu Ambararacmi Padangratha; Gusti Ayu Kadek Diah Puspawati; I Gede Arie Mahendra Putra (Study Program of Food Technology, Faculty of Agricultural Technology, Udayana University, 2026)
Jeruju leaves are types of mangrove plants that contain phenolic compounds and have been developed as powdered instant drink using maltodextrin encapsulant. Maltodextrin has poor viscosity after applied as encapsulant so it can be combined with encapsulants like glucomannan. The used material can affect the concentration of maltodextrin and glucomannan needed to achieve the product with best characteristics. This research aims to know the effects of maltodextrin and glucomannan concentration on the characteristics of jeruju leaves instant drink powder, and the right maltodextrin and glucomannan concentration to achieve the product with the best characteristics. This research uses Completely Randomized Design Factorial with two factors namely: 1) maltodextrin concentrations (10%; 20%) and 2) glucomannan concentrations (0%; 0.5%; 0.75%; 1%), the repetitions were done twice. The data was analyzed using an Analysis of Variance, if the treatment affects the observed variable, it will be continued with Duncan Multiple Range Test. The result shows that the interaction between maltodextrin and glucomannan had real impact on total phenolic compound, encapsulation efficiency, and antioxidant activity. Each maltodextrin and glucomannan concentration had real impact on yield, meanwhile maltodextrin concentration individually had real impact on ash content and dissolving time. The concentration of 20% maltodextrin and 0.75% glucomannan results in jeruju leaves instant drink powder with the best characteristics: yield 18.48%, water content 3.99%, ash content 1.54%, total phenolic compound 9.19 mg GAE/100g, encapsulation efficiency 84.09%, antioxidant activity 66.38%, dissolving time of 2.54 minutes, color, aroma, taste, and overall acceptance showed slightly liked score.